Back Cover: Filling the Gaps in the Challenging Asymmetric Hydroboration of 1, 1‐Disubstituted Alkenes with Simple Phosphite‐Based Phosphinooxazoline Iridium Catalysts (ChemCatChem 1/2015). Issue 1 (January 2015) - Magre, Marc; Biosca, Maria; Pàmies, Oscar; Diéguez, Montserrat
<x xml:space="preserve">Abstract</x> The cover picture shows the asymmetric hydroboration of challenging 1, 1‐disubstituted olefins by using phosphinooxazoline‐based phosphite‐oxazoline iridium ligands. In their Full Paper, M. Magre, M. Biosca et al. show that introducing the biaryl phosphite moiety in ligand design is highly adventitious in terms of substrate versatility. The 3 D structure of the phosphite‐based phosphinooxazoline ligand is a graphical representation rather than a known structure. The article highlighted by this cover can be found on p. 114 ff. of Issue 1, 2015.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>